Computer simulations of the dynamic properties of methane in a model silica gel - Patsahan, T.; Trokhymchuk, A.; Holovko, M. (Condensed Matter Physics, 2003)
Molecular dynamics (MD) simulations are reported for a Lennard-Jones fluid adsorbed into a model silica gel to study the dynamic properties of the adsorbed methane molecules. The mean-square displacement and velocity autocorrelation function of the adsorbed molecules are calculated for a set of supercritical temperatures at low (gas-like) and high (liquid-like) fluid densities and compared with the same data for a bulk fluid. The evaluated radial distribution functions illustrate the formation of a contact layer on the pore surface that is consistent with the decrease in the mobility of the adsorbed molecules in a porous environment. The calculated self-diffusion coefficient indicates a good quantitative agreement with the measured data for methane confined to the silica gel.